PG education at IIHR... Present and future prospects - Venugopalan, R; Dinesh, M R; Janakiram, T (Indian Horticulture, 2019)
The Postgraduate School of Horticultural Sciences at IIHR, Bengaluru, is presently offering Ph.D. degree in the disciplines of Fruit Science, Vegetable Science, Floriculture and Landscape Architecture and Post-Harvest Technology, with a total of 30 students on roll. Subsequently, 115 scientists across 22 disciplines and 22 scientists in Horticulture have been recognized by the IARI, New Delhi, as faculty to impart teaching and to guide students in their research, respectively. The PG programme is in-house and all the basic facilities required for the students such as hostel, classroom, library, playground, recreation facilities etc. have been created at the IIHR campus itself. The Board of Studies, implements the desired courses and students’ grades are extensively monitored online by using the IARI PG School management system. Apart from this, IIHR is also offering postgraduate and doctorate courses in horticulture and different subjects of University of Horticultural Sciences (Bagalkot) and guide postgraduate students through the MOU, leading to the award of M.Sc. and Ph.D. in Horticulture and allied disciplines.